THE INFLUENCE OF AGE, WORKING HOURS, ONLINE OJEK RATES POLICY AND EDUCATION ON INCOME LEVELS OF GRABBIKE DRIVERS IN MEDAN EAST SUBDISTRICT IN THE PERSPECTIVE OF ISLAMIC ECONOMY - Apriliana, Putri (Al-Muhtarifin: Islamic Banking and Islamic Economic Journal, 2023)
The aspects of the problem studied by the author are regarding the influence of Age, Working Hours, Tariff Policy and Education on the income of grabbike drivers in East Medan District. The purpose of this study is to determine the effect of age, working hours, tariff policies and education on the income level of grabbike drivers, this study uses a quantitative approach. Data collection was carried out by distributing questionnaires using non-probability sampling techniques with accidental sampling methods for 80 respondents and the results of the questionnaires were received back for processing. The data were analyzed using SPSS 25. The results of the research based on the t test showed that age, working hours, tariff policies and education had a positive and significant effect on the income of grabbike drivers in Medan Timur District.